Ensaios de avaliações de programas federais: assistência farmacêutica e mobilidade acadêmica - Barbosa, Gerrio dos Santos (2022)
This doctoral thesis develops two essays related to public policy evaluation, the first one about the Brazilian Popular Pharmacy Program (BPPP) and the second about the Sciences Without Borders (SwB). The first essay address how a reduction on subsidies by the federal government affected access and demand for medicines in the BPPP in terms of copayments in partnerships with private pharmaceutical establishments. To do so, we use administrative data from the BPPP aggregated at the level of mesoregions in Brazil, spanning the period from January 2015 to December 2017. Thoses subsidies became effective as of Dezember 2016, thus enabling the use of the quasi-experimental method of differences in differences (DiD) for capture exogenous effects and diagnose possible heterogeneities in the Program. The main results indicate that the reduction in the amounts subsidized by the federal government reduced the access of beneficiaries and the demand in the Program, with a drop of 26% and 24%, respectively. The poorest Brazilian regions had an average reduction of about 46% in demand and 41% in access to medicines. The second essay addresses how SwB affected quantitative and qualitative academic production outcomes using an entropy balancing method combined with a linear regression model. We use several data sets, such as the Lattes Platform which include information for brazilian academics, to build outcome indicators and covariates, including those that influence the self-selection of SwB scholarship holders. The treated group is composed of SwB scholarship holders of sandwich doctorate and the non-treated group are scholarship holders who completed their doctorate in Brazil (without participating in the SwB). The entry period for both groups span the period between 2011 and 2016. The main results indicated that SwB scholarship holders do not differ from those not benefited by the Program in terms of academic productivity, either in terms of quantity of publications and patents or regarding the quality of publications. The results for robustness check and heterogeneities analysis are in line with the main results, but there are some indicators in which the scholarship holders in Brazil have higher productivity than scholarship recipients awarded by the SwB.